DESAIN PERMAINAN ANAK USIA DINI UNTUK MENSTIMULASI LOGIKA MATEMATIKA - Betanursanti, Ida; Ngarifah, Siti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Gombong, 2023)
The problem faced by early childhood teachers is that there are still some children whose mathematical logic intelligence un-optimally developed. This happens because in the learning process they are rarely using a game as the learning media to stimulate mathematical logic intelligence. This study aims not only to identify the information of what are children's games stimulating intelligence and mathematical logic in early childhood but also to determine the types of games and performance validation tests.The research method is using Kansei Engineering type first. Begin with the determinate of the domain to make specifications for the game that will be researched and designed. Determining the Kansei words through a questionnaire then sorted by using differential semantics. The results are implementing in the form of a game. Furthermore, homogeneity and normality tested used the chi-square. The results obtained by the chi-square counting greater than 0.05, mean that there is a type of game with the stimulus of intelligence and mathematical logic in early childhood.